(untitled) (Comillas Journal of International Relations, 2020)
Populism is not a monolithic phenomenon. The circumstances in which it stops having marginal representation and reaches considerable power vary depending on a number of preconditions. And, since populism arises from different realities in various societies, the materialization of such a phenomenon may also adopt opposing ideological nuances. This study hence argues that the triumph of left-wing populism is irremediably preceded by an organic crisis. Considering the cases of Chávez and Tsipras, it is suggested that both of these populisms came to power riding on an impoverished population; the economic recession would undermine the bases of the democratic order, thus propelling popular rejection towards the institutions responsible for such a disaster and liquidating the established order of legitimacy. The organic crisis becomes imminent: the desire to refound a decrepit order prevails throughout society, and left-wing populism emerges to harangue the “people” against the “non-people” while electorally capitalizing such a situation.